Simultaneous detection of pork and wild boar meat in chicken sausages using the combination of a single primer and real-time polymerase chain reaction (qPCR) - Nurull Hikmah; Rumiyati Rumiyati; Sismindari Sismindari; Abdul Rohman (Universitas Ahmad Dahlan, 2020)
The identification of meat species in food products and pharmaceuticals is vital to minimize food adulteration practices. Due to its specificity, polymerase chain reaction (PCR)-based methods are the most commonly reported methods for detection of food adulterants. This study was aimed to evaluate the use of real-time PCR with a species-specific primer to identify two non-halal types of meat, namely pork and wild boar meat (WBM), in chicken sausages. The primer was designed using online software PrimerQuest from NCBI (National Center for Biotechnology Information) to target the mitochondrial ND1 gene of Sus scrofa domestica. The annealing temperature (Ta) of the primer used during real-time PCR analysis was optimized to achieve the highest response fluorescence unit at the lowest cycles. Real-time PCR using the primers of NK-ND1-Ssc1 (Forward: 5’ AAAGGACCCAACGTTGTAGG 3’ and Reverse: 5’ TAGTGCTAGGGATAAGGCTAGG 3’) was validated with several parameters, namely specificity, the limit of detection for sensitivity, linearity, efficiency, and repeatability. The optimum annealing temperature of NK-ND1-Ssc1 was 58.1oC. The sensitivity evaluation revealed that the limits of detection (LoD) of pork and WBM in reference sausage samples containing 100% pork and WBM were 500 pg and 50 pg, respectively, which correspond to 0.3% meat in sausage products. The efficiency values of real-time PCR amplification were 93.1% and 94.8% for pork and WBM with coefficient variations of 0.2884% and 0.4998%, respectively. The validated method was subsequently applied to analyze the commercial samples, and among the twelve (12) samples evaluated, there was one sample positive of containing non-halal meat (pork or WBM). Real-time PCR using species-specific primers, e.g., NK-ND1-Ssc1, is specific and sensitive; therefore, this method can be used as an alternative technique for authentication of halal meat.